Review of One Health in the Galápagos Islands (Part 2): climate change, anthropogenic activities, and socioeconomic sustainability - Vega-Mariño, Patricio A.; Jimenez, Isabel A.; Villacres, Tamia; Houck, Emma L. (Frontiers in Conservation Science, 2024)
The Galápagos archipelago is a vast reservoir of terrestrial and marine biodiversity and is particularly susceptible to human, animal, and environmental impacts. Climate change, globalization, and the blurring of human-domestic animal-wildlife interfaces are poised to bring new threats and challenges to the region. A One Health perspective that simultaneously considers human, animal, and environmental health is imperative in assessing and mitigating the challenges facing the Galápagos Islands. Many challenges facing biodiversity in the Galápagos Islands can ultimately be linked to anthropogenic factors. In Part I of this review, we reviewed the impacts of invasive species and identified infectious diseases of importance. In Part II of this review, we discuss the impacts of climate change and ocean acidification, and highlight the effects of several direct anthropogenic activities, including tourism, overfishing, pollution, land use, and human-wildlife conflict. We also review the socioeconomic and political context of the Galápagos Islands, including current challenges in water and energy use, sanitation, and economic stability. We examine the importance of investment in local development for building resiliency and sustainability in the archipelago. Finally, we discuss the impact of the COVID-19 pandemic in the region. Throughout this two-part review, we build a cohesive picture of One Health in the Galápagos Islands by integrating past work, current needs, and emerging threats. We also consider overarching goals for conservation, ecosystem management, and socioeconomic sustainability that have been previously defined by both governmental and non-governmental stakeholders, and identify discrete, implementable, and interdisciplinary recommendations that will facilitate achievement of those goals.